1983
DOI: 10.1136/gut.24.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic ingestion and other factors preceding relapse in ulcerative colitis.

Abstract: SUMMARY To investigate factors which predispose to relapse in patients with ulcerative colitis, we conducted a survey to compare the events occurring in the four weeks preceding the clinic attendance of 62 outpatients in remission with those taking place in the same period before the onset of relapse in 21 patients attending with active disease. The only event which occurred significantly more often in patients who subsequently relapsed was ingestion of paracetamol and other inhibitors of prostaglandin synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
2
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(62 citation statements)
references
References 10 publications
1
56
2
1
Order By: Relevance
“…The incidence of these lesions has not been determined, especially in the United States where the use of NSAID suppositories is rare. NSAID-related complications have been reported in patients with pre-existing diverticulosis (116,117) and inflammatory bowel disease (119,120). In a controlled prospective study evaluating both complications of diverticulosis and perforation, it was found that 31 of 92 patients with complicated diverticular disease were taking NSAIDs, and this was significantly greater than the age-matched control group.…”
Section: Ajg -November 1998mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of these lesions has not been determined, especially in the United States where the use of NSAID suppositories is rare. NSAID-related complications have been reported in patients with pre-existing diverticulosis (116,117) and inflammatory bowel disease (119,120). In a controlled prospective study evaluating both complications of diverticulosis and perforation, it was found that 31 of 92 patients with complicated diverticular disease were taking NSAIDs, and this was significantly greater than the age-matched control group.…”
Section: Ajg -November 1998mentioning
confidence: 99%
“…There are some data to indicate that NSAIDs may have a detrimental effect on patients with inflammatory bowel disease and in patients previously in remission, inducing a relapse only a few days after starting NSAIDs (119,120). A recent case-control study of 200 hospital admissions for acute inflammatory bowel disease showed that the overall odds ratios for current and recent exposure to NSAIDs were 1.77 and 1.93, respectively, when compared with 1198 community controls (121).…”
Section: Ajg -November 1998mentioning
confidence: 99%
“…Concurrent infection in colitic patients can complicate differential diagnosis, and pa tient management can be problematic [8], Many factors have been implicated in pre cipitating relapse of chronic ulcerative colitis although conclusions from different studies are often conflicting. Of particular interest in a microbiological context is the not infre quent observation that a relatively trivial in fection immediately preceeds relapse, most commonly an upper respiratory tract infec tion [9][10][11][12][13] or gastroenteritis [II]. These cor relations are supported by other, associated, risk factors such as recent foreign travel [11].…”
mentioning
confidence: 62%
“…These cor relations are supported by other, associated, risk factors such as recent foreign travel [11]. treatment with antibiotics [11] and use of analgesics [13]. This paper describes a study designed to re-examine the role of enteric infection in ulcerative colitis by retrospective study of an unselected patient group present ing at primary referral clinics with active dis ease.…”
mentioning
confidence: 95%
“…An important factor in choosing treatment methods is the evaluation of disease activity; this is commonly done using clinical criteria based on symptoms [9] owing to its convenience and noninvasiveness. When clinical criteria are used alone, however, 40% of patients in whom remission is achieved relapse within 1 year [10,11] . This finding indicates the need for colonoscopic and histopathologic assessment also, notwithstanding their disadvantages, including inconvenience, invasiveness and prolongation of the colonoscopic examination.…”
Section: Introductionmentioning
confidence: 99%